Bimbingan Belajar Membaca Al-Qur’an bagi Lansia: Kajian Perspektif Andragogi - Fauzatin Ni’mah; Ermalianti Ermalianti; Anita Ariani (Lembaga Yasin AlSys, 2025)
The concerns of elderly members at Majelis Taklim Syamsul Hidayah Banjarmasin regarding their fluency in reading the Qur’an, especially after gaining awareness of the importance of correct recitation in prayer form the background of this study. The objective is to describe the learning process, instructional methods employed, and challenges faced by the elderly in Qur’an reading guidance sessions. This research adopts a case study method, with data collected through interviews and observations. The findings reveal that the learning process comprises three stages: an opening with the recitation of istighfar, a core activity involving turn-based reading of Iqro or the Qur’an, and a closing prayer together. The instructional methods include the Iqro method, a gentle and personalized motivational approach, an informative method involving repeated explanations, and a participatory method that actively engages the elderly learners. The challenges encountered include memory limitations, cognitive decline, speech difficulties, visual recognition issues of Arabic letters, and other physical constraints. The study concludes that Qur’an instruction for the elderly requires the application of andragogical principles tailored to their psychological and physical conditions. The implications of this research contribute to the development of age-friendly Qur’an learning models and offer a reference framework for other majelis taklim in designing similar programs.